Range-wide trends in tiger conservation landscapes, 2001 - 2020 - Sanderson, Eric W.; Miquelle, Dale G.; Fisher, Kim; Harihar, Abishek; Clark, Chris; Moy, Jesse; Potapov, Peter; Robinson, Nathaniel; Royte, Lucinda; Sampson, Dustin; Sanderlin, Jamie; Yackulic, Charles B.; et al. (Frontiers in Conservation Science, 2023)
Of all the ways human beings have modified the planet over the last 10,000 years, habitat loss is the most important for other species. To address this most critical threat to biodiversity, governments, non-governmental actors, and the public need to know, in near real-time, where and when habitat loss is occurring. Here we present an integrated habitat modelling system at the range-wide scale for the tiger (Panthera tigris) to measure and monitor changes in tiger habitat at range-wide, national, biome, and landscape scales, as often as the underlying inputs change. We find that after nearly 150 years of decline, effective potential habitat for the tiger seems to have stabilized at around 16% of its indigenous extent (1.817 million km2). As of the 1st of January 2020, there were 63 Tiger Conservation Landscapes in the world, covering 911,920 km2 shared across ten of the 30 modern countries which once harbored tiger populations. Over the last 20 years, the total area of Tiger Conservation Landscapes (TCLs) declined from 1.025 million km2 in 2001 to 911,901 km2 in 2020, a range-wide loss of 11%, with the greatest losses in Southeast Asia and southern China. Meanwhile, we documented expansions of modelled TCL area in India, Nepal, Bhutan, northern China, and southeastern Russia. We find significant potential for restoring tigers to existing habitats, identified here in 226 Restoration Landscapes. If these habitats had sufficient prey and were tigers able to find them, the occupied land base for tigers might increase by 50%. Our analytical system, incorporating Earth observations, in situ biological data, and a conservation-oriented modelling framework, provides the information the countries need to protect tigers and enhance habitat, including dynamic, spatially explicit maps and results, updated as often as the underlying data change. Our work builds on nearly 30 years of tiger conservation research and provides an accessible way for countries to measure progress and report outcomes. This work serves as a model for objective, range-wide, habitat monitoring as countries work to achieve the goals laid out in the Sustainable Development Goal agenda and Global Biodiversity Framework of the Convention on Biological Diversity.